Job satisfaction of company doctors - all is well except recognition? Berufszufriedenheit in der Arbeitsmedizin - alles gut, nur keine Anerkennung? - Amler, N.; Quittkat, C.; Sedlazcek, S.; Nesseler, T.; Letzel, S.; Drexler, H. (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2020)
Objective: The aim of this paper is to examine job satisfaction among company doctors in the German-speaking area. Moreover, we analysed the extent to which various sociodemographic data and specific occupational contexts have an influence on job satisfaction and to what extent the individual groups differ in this respect. Methods: The present study is based on the company doctor survey conducted as part of a large-scale care research project in Germany. The survey was designed as a cross-sectional study and took place from September 2017 to April 2018. The survey was conducted online and on paper. The data was prepared and analysed mainly by using descriptive statistical methods. Results: The majority of the doctors questioned seem to be happy with their occupation as company doctor. Company doctors were especially positive about the focus on prevention (67%), the working hours (63%), the meaningfulness (59%) and the attractiveness of the subject (57%). Company doctors found the lack of recognition by colleagues to be one of the particularly negative aspects of their occupation, with 50% of those questioned highlighting this as a negative factor. These findings hold for the most part irrespective of age, gender and occupational context. Conclusion: It is important to work on the occupational profile of company doctors in order to counteract the lack or absence of recognition and to educate the public and professionals in a targeted manner. A start should be made with medical students to this end. Above all, it is important to emphasise the preventive character of the subject and the opportunities provided by what is plainly the largest setting for the practice of prevention. In this connection, it is also important to exploit the opportunities provided within the scope of the Prevention Act.
CRIS-Team Scopus Importer:2024-12-16
Keywords: appreciation; job satisfaction; payment; prevention; recognition